Relevant statistical observations in the basketball competitions of 2014 and 2019 Men`s Basketball World Cups - Stavropoulos, N. (Journal of Physical Education and Sport, 2020)
The objective of this study is to determine whether there are any significant discrepancies between the parameters that affect qualification to the next round up to the Final Four between men's national teams in 2014 and 2019 FIBA World Cups. All matches (n = 168) undertaken during 2014 and 2019 World Cups (Spain, n =76; China, n = 92) were examined. In 2014, national teams played more inside game and scored over 30 in the paint out of 85.29 total points. The teams scored more than 25 points from the bench because there were starting players and substitutes coming from the bench. However, during the 2019 World Cup, the game seemed to move from the paint to perimeter, attempting 3-point field goals, and scoring more than 24 points per match compared to the teams that were disqualified. Moreover, the teams that qualified to the final round appeared to use more than 15 assists owing to the better ball movement during the attack. In addition, greater attention is paid to free throws, with a success rate of over 73%. Finally, defensive pressure on opponents increased because the teams scored more than 10 points from opponent turnovers.